From Collective Ritual to Social Cohesion: Explaining Social Capital Reproduction through Nyacarkeun Jalan - Rangga Eka Prasetya; Alpin Alpin; Egi Nurholis (Universitas Galuh, 2026)
Collective rituals continue to shape social relations in many rural communities, yet the mechanisms through which they reproduce social capital remain insufficiently explained in studies of local traditions. Existing scholarship has primarily documented the cultural values embedded in traditional practices, while the processes connecting ritual participation, social trust, collective norms, and social cohesion have received limited analytical attention. This study examines how the Nyacarkeun Jalan tradition reproduces social capital in a Sundanese rural community through an intrinsic qualitative case study conducted in Dusun Linggaharja, Ciamis, Indonesia. Data were collected through participant observation, in-depth interviews with nineteen purposively selected informants, and document analysis, followed by interactive analysis using the Miles, Huberman, and Saldaña framework. The findings indicate that repeated participation in collective rituals generates social trust, reinforces norms of reciprocity and shared responsibility, expands intergenerational social networks, and strengthens community cohesion. The study proposes a mechanism of social capital reproduction through collective ritual, integrating the complementary perspectives of Bourdieu, Coleman, and Putnam. This conceptual contribution positions local tradition as an enduring institutional process for sustaining collective action and rural social resilience amid contemporary social transformation.